EFFECT OF DHAINCHA AND SUNNHEMP HAY INCORPORATED TOTAL MIXED RATION ON GROWTH PERFORMANCE AND COST EFFECTIVENESS OF MECHERI LAMBS - D. Santhiya; N. Bharathy; D. Anandha Prakash Singh; P. Vasanthakumar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The study evaluated the effect of incorporating dhaincha (Sesbania aculeata) and sunnhemp (Crotalaria juncea) hay in total mixed ration (TMR) on growth performance and cost effectiveness of Mecheri lambs. Twenty-four weaned lambs (3 - 4 months) were allotted to four dietary treatments and fed for 120 days, comprising TMR with 20% hedge lucerne hay (Desmanthus virgatus) as control, 20% dhaincha hay (Sesbania aculeata), 20% sunnhemp hay (Crotalaria juncea), and a combination of 10% dhaincha hay (Sesbania aculeata) + 10% sunnhemp hay (Crotalaria juncea), with all diets formulated to be iso-nitrogenous and iso-caloric and offered ad libitum. Daily feed intake and fortnight body weight were recorded and the economic parameter was calculated at the end of the trial. The results showed no significant differences (P > 0.05) in body weight gain among the treatment groups. Although the dry matter intake was higher in the control group, the legume-based diets were maintained with comparable intake. Economic analysis indicated the lower feed cost and higher net income in lambs fed dhaincha based TMR. The study was concluded that the dhaincha and sunnhemp hay can be used as cost-effective protein-rich alternatives to hedge lucerne hay in TMR based Mecheri lamb production systems.